The Potential of Mangongkal Holi as a Cultural Tourism Destination - Tobing, Suzen Hartaty Rotoea (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
Mangongkal holi is a secondary burial ritual of the Toba Batak tribe that can only be performed in the hometown of each clan located around Lake Toba. As the highest ritual in Toba Batak customs, Mangongkal Holi is a representation of the cultural identity of the Toba Batak tribe. Based on this, Mangongkal Holi can be an integral part in relation to the government's efforts to revitalise Lake Toba as a tourist destination. This article aims to analyse the potential of the Mangongkal Holi ritual as a cultural destination. The results of the analysis prove that the presence of dance, percussion, and ritual performance elements in the mangongkal holi procession of mangongkal holi has the potential as a cultural tourism destination for national and international tourists. The implementation of mangongkal holi also has an impact on the creative economy industry at the location of implementation. However, the potential of mangongkal holi as a cultural tourism destination is hampered by an unstructured implementation schedule and socialisation of ritual implementation which tends to be exclusive to the Batak toba clan.